General and Specific Contributions of RAN to Reading and Arithmetic Fluency in First Graders: A Longitudinal Latent Variable Approach - Hornung, Caroline; Martin, Romain; Fayol, Michel (Frontiers in Psychology, 2017)
In the present study we opted for a longitudinal design and examined RAN performance from two perspectives. In a first step, we examined the structure of rapid automatized naming (RAN) performance from a general cognitive perspective. We investigated whether rapid naming measures (e.g., digit RAN, color RAN) reflect a mainly domain-general factor or domain-specific factors. In a second step we examined how the best fitting RAN model was related to reading and arithmetic outcomes, assessed several months later. Finally in a third step we took a clinical perspective and investigated specific contributions of RAN measures to reading and arithmetic outcomes. While RAN has emerged as a promising predictor of reading, the relationship between RAN and arithmetic has been less examined in the past. Hundred and twenty-two first graders completed seven RAN tasks, each comprising visually familiar stimuli such as digits, vowels, consonants, dice, finger numeral configurations, objects and colors. Four months later the same children completed a range of reading and arithmetic tasks. From a general cognitive perspective, structural equation modeling supports a one-dimensional RAN factor in 6-to-7-year-old children. However, from a clinical perspective, our findings emphasize the specific contributions of RANs. Interestingly, alphanumeric RANs (i.e., vowel RAN) were most promising when predicting reading skills and number-specific RANs (i.e., finger numeral configuration RAN) were most promising when predicting arithmetic fluency. The implications for clinical and educational practices will be discussed.